Perubahan Budaya Organisasi Pendidikan dalam Pembentukan Karakter Siswa di Tingkat MA Bina Mulia - Nayla Maulidya; Ardian Pramandoko; Hasyim Asy’ari (CV. Kalimasada Group, 2026)
This study aimed to examine changes in educational organizational culture in shaping student character at a Madrasah Aliyah, its effectiveness, and the surrounding supporting and inhibiting factors. A descriptive qualitative approach was used to analyze data obtained from in-depth interviews with the Head of the Madrasah and the Islamic Religious Education (PAI) teacher. The findings indicated that changes in organizational culture were implemented through structured religious habituation programs, such as mandatory congregational prayers three times a day (Dhuha, Dzuhur, Ashar), morning Al-Qur'an literacy (BTQ), bi-weekly Muhadhara forums, and specific surah memorization targets as graduation prerequisites. These habituations successfully improved students' discipline and morals, although teachers still had to remain proactive in guiding less responsive students. Continuous rule socialization, a strong culture of deliberation, and the active involvement of parents and community leaders served as the key supporting factors for school culture implementation. Meanwhile, the inhibiting factors faced by the madrasah included short-noticed activity planning, diverse student behavioral backgrounds, and weather constraints during congregational prayers.